Reproductive Aspects of Moenkhausia intermedia Eigenmann, 1908 (Pisces, Characidae) in the Upper Paraná River Basin, Brazil. (30th June 2011) - Casimiro, Armando César Rodrigues; Garcia, Diego Azevedo Zoccal; de Almeida, Fernanda Simões; Orsi, Mário Luís
Abstract : The aim of this work was to determine the reproductive tactic of the population of Moenkhausia intermedia, inhabiting the Capivara Reservoir, lower Paranapanema River. Four different stretches of the reservoir were selected, and sampling was carried out quarterly, in the period from 2001 to 2004. Fish were captured utilizing gill nets, cast nets, and seine nets. Later, fish were identified and measured and had their sex identified. Here we describe sex proportion, standard length at first maturation (L 50 ), site and period of spawning, fecundity and type of spawning. The population showed an effective reproductive activity in the area, with the number of females higher than males andL 50 corresponding to 6, 1 cm and 5, 5 cm, respectively. A greater intensity of spawning occurred in the warmest months. Reproductive activity was identified in all stretches studied, and the absolute fecundity average was 9611 oocytes per gonad, and the mean relative fecundity corresponded to 1065 oocytes/grams.